2004
DOI: 10.1046/j.1398-9995.2003.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of a major allergen from Cupressus arizonica pollen, Cup a 3, a PR‐5 protein expressed under polluted environment

Abstract: Cup a 3 is a PR-5 protein derived from C. arizonica pollen. The expression of the protein under polluted conditions has a direct incidence on the pollen allergenicity, as has been demonstrated by skin tests and Radioallergosorbent test inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 35 publications
(41 reference statements)
3
70
0
8
Order By: Relevance
“…Thaumatins, other plant defence proteins, have been found that are more intensely expressed in response to environmental attacks (Cortegano et al, 2004;Suárez-Cervera et al, 2008b). The effect of air-pollution on pollen grains as well the effects of diverse treatments and other environmental aggressions on fruits explain the increased expression of nsLTPs, which can affect the health of the inhabitants in developed countries (Salcedo et al, 2007).…”
Section: Nsltps In Plant Food and Pollen Grainsmentioning
confidence: 99%
“…Thaumatins, other plant defence proteins, have been found that are more intensely expressed in response to environmental attacks (Cortegano et al, 2004;Suárez-Cervera et al, 2008b). The effect of air-pollution on pollen grains as well the effects of diverse treatments and other environmental aggressions on fruits explain the increased expression of nsLTPs, which can affect the health of the inhabitants in developed countries (Salcedo et al, 2007).…”
Section: Nsltps In Plant Food and Pollen Grainsmentioning
confidence: 99%
“…Overexpression of TLPs appears to enhance resistance to fungal disease (Liu et al 1994;Zhu et al 1996;Chen et al 1999). Moreover, TLPs in various plant-derived foods (Hoffmann-Sommergruber 2002) and conifer pollen (Midoro-Horiuti et al 2000;Cortegano et al 2004) are allergens.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that Cry j 3 is an important allergen in some patients. It has been reported that the expression level and allergenic activity of TLPs vary under different environmental conditions (20). Therefore, the importance of Cry j 3 as a Japanese cedar allergen may differ among years and locations.…”
Section: Discussionmentioning
confidence: 99%